Pengukuran Kualitas Layanan di Universitas Kristen Indonesia (UKI) - Freddy Simbolon (Binus Business Review, 2012)
The purpose of this study was to determine the service quality that was held by UKI based on student’s perceptions. The method used in this study is the survey method on UKI’s students using questionnaires. The statement in the questionnaires were arrange based on the five dimensions of service quality. Those were tangibles, responbilities, assurances, realibilities, and emphathy. The servqual analysis shows that all attributes get a negative response which means that student’s perception is less than the student’s expectations. The IPM shows attributes that need to get first priority to be improved are library facilities more complete, lecturing process more interactive, handling complaints about the lectures properly, the tuition in accordance with benefits, and the librarian serve students with friendly.